2007
DOI: 10.1002/rra.971
|View full text |Cite
|
Sign up to set email alerts
|

Point source effects on density, biomass and diversity of benthic macroinvertebrates in a Mediterranean stream

Abstract: We sampled benthic macroinvertebrates above and below a point source effluent in La Tordera stream (NE, Spain) over [2001][2002] to assess the effects of nutrient enrichment on the structure, and taxonomic composition of the benthic macroinvertebrate community. Below the point source, discharge, specific conductance and nutrient concentrations were higher than at the upstream reach, while dissolved oxygen (DO) decreased. Macroinvertebrate density was higher at the downstream reach than at the upstream reach on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 54 publications
5
38
0
Order By: Relevance
“…It has been reported that floods could have an important role in stream habitat recovery (Ortiz and Puig 2007). In this study, it is probable that the flood of July 2006 contributed to the recovery of species richness and density observed after the dam removal.…”
Section: Discussionmentioning
confidence: 68%
“…It has been reported that floods could have an important role in stream habitat recovery (Ortiz and Puig 2007). In this study, it is probable that the flood of July 2006 contributed to the recovery of species richness and density observed after the dam removal.…”
Section: Discussionmentioning
confidence: 68%
“…Macroinvertebrates have been widely used as bioindicators in impact studies of environmental perturbations on aquatic ecosystems (Lenat et al 1981;Victor & Ogbeibu, 1985;Ortiz & Puig, 2007;Olomukoro & Dirisu, 2014), water quality assessments (Sharma & Rawat, 2009), and organic and inorganic pollution monitoring studies (Thorn & Williams, 1997;Kazanci & Dugal, 2000). Macroinvertebrates are thus useful to understanding the ecological health of an aquatic ecosystem and can complement, and even become an alternative to, chemical and microbiological analyses, because they are sensitive to short-term fluctuations of the aquatic health (Ravera, 2000;Ikomi et al 2005;George et al 2009;Olomukoro & Dirisu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This can explain the results of the present study, once it was predictable that presented a higher value in downstream of WWTP due to organic contamination. With regard to f EPT and %EPT, their values decreased with the increase of nutrients (Barbour et al 1996;Ortiz and Puig 2007), heavy metals (Lillie et al 2003), input of sediments (Meban 2001), among others. These metric values were low in the downstream site, corroborating the IBMWP and BBI values that showed a better water quality in the upstream site.…”
Section: Discussionmentioning
confidence: 95%
“…In a similar study, Ortiz and Puig (2007) evaluated the nutrient enrichment effects of WWTP of Sta. Maria of Palautordera (River La Tordera-NE Spain) in the macroinvertebrate community structure and taxonomic composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation